A multi-stage multi-criteria hierarchical decision-making approach for sustainable supplier selection - Hendiani, Sepehr; Mahmoudi, Amin; Liao, Huchang (Applied soft computing, 2020)
Sustainable supplier selection is known as a crucial objective in supply chains due to its impact on profitability, adorability, flexibility, and agility of the system. This study proposes a new multi-stage hierarchical fuzzy index-based approach with which decision-makers are empowered to select the most sustainable supplier based on sustainability triple bottom line criteria. Besides, a new fuzzy extension for the best-worst method is proposed considering trapezoidal fuzzy membership functions that can cover uncertainty under imprecise environments. This study makes a contribution to the literature of sustainable supply chains in the sense that it facilitates the computational complexity of previous decision-making approaches by collecting the most relevant criteria and a straightforward fuzzy process. Besides, the graded mean integration representation method has been adopted for prioritizing the supplier based on their performance of sustainable development, which enhances the accuracy of selection compared with previous ranking methods. The proposed study can be utilized as a benchmark for sustainability evaluations between suppliers. A real-world case study is resolved to illustrate the superiority and broad application of the proposed model. •The sustainability triple bottom line (TBL) attributes are distinguished.•The fuzzy Best-Worst method is adopted to obtain corresponding weights.•A new fuzzy sustainable supplier index is proposed by fuzzy aggregation operator.•A new ranking method is utilized to select the most sustainable supplier.